Free movement of labour in the single European market - Heinz Werner (Intereconomics, 1990)
Improving the mobility of labour is a major component of Project 92. What are the reasons for migration under conditions of freedom of movement and what are the repercussions for the labour market?
Keywords: 330; European Community